Responses of Japanese Cenozoic molluscs to Pacific gateway events - Kenshiro Ogasawara (Revista Mexicana de Ciencias Geológicas)
The Cenozoic history of Pacific Ocean gateways can be divided into seven stages, extending from the Eocene onset of the Tasmanian seaway to the Pliocene closure of the Central American seaway. The first stage was the interval before 43 Ma, tentatively named the proto-Tasmanian stage. Development of the Tasmanian seaway (43-29 Ma) occupied the second stage. The third stage (29-23.5 Ma) was the oceanographically and paleoceanographically most open system, because the Pacific was not isolated from other oceans. The 4th stage consists of the closing of the Bering Strait prior to closure of the Indonesian seaway (23.5-17 Ma). The 5th stage was the time during which the Indonesian and Bering Seaways were both closed (17-5 Ma). The 6th stage consisted of a closed Indonesian seaway, and an open Bering Strait and Central American seaway (5 -2 Ma). The 7th and final stage is the modern situation, with a closed Central American seaway.